Initial lung transplantation experience with uncontrolled donation after cardiac death in North America. Issue 6 (29th February 2020) - Healey, Andrew; Watanabe, Yui; Mills, Caitlin; Stoncius, Michele; Lavery, Susan; Johnson, Karen; Sanderson, Robert; Humar, Atul; Yeung, Jonathan; Donahoe, Laura; Pierre, Andrew; de Perrot, Marc; et al.
Abstract : Uncontrolled donation after cardiac death (uDCD) has the potential to ameliorate the shortage of suitable lungs for transplant. To date, no lung transplant data from these donors are available from North America. We describe the successful use of these donors using a simple method of in situ lung inflation so that the organ can be protected from warm ischemic injury. Forty‐four potential donors were approached, and family consent was obtained in 30 cases (68%). Of these, the lung transplant team evaluated 16 uDCDs on site, and 14 were considered for transplant pending ex vivo lung perfusion assessment. Five lungs were ultimately used for transplant (16.7% use rate from consented donors). The mean warm ischemic time was 2.8 hours. No primary graft dysfunction grade 3 was observed at 24, 48, or 72 hours after transplant. Median intensive care unit stay was 5 days (range: 2‐78 days), and median hospital stay was 17 days (range: 8‐100 days). The 30‐day mortality was 0%. Four of 5 patients are alive at a median of 651 days (range: 121‐1254 days) with preserved lung function. This study demonstrates the proof of concept and the potential for uDCD lung donation using a simple donor intervention. Abstract : The authors describe a successful lung transplantation from uncontrolled donation after cardiac death. Van Raemdonck et al's editorial is on page 1475 .